Bioactive compound profile of sun-dried cubeb (Piper cubeba) fruit extract - RENDI FATHONI HADI; KUSTANTINAH KUSTANTINAH; MUHLISIN MUHLISIN; RONNY MARTIEN (Biodiversitas Journal of Biological Diversity, 2025)
Abstract. Hadi RF, Kustantinah, Muhlisin, Martien R. 2025. Bioactive compound profile of sun-dried cubeb (Piper cubeba) fruit extract. Biodiversitas 26: 662-669. Piper cubeba is a herbal plant that is commonly used to treat digestive and respiratory diseases because it has biological activity related to bioactive compounds. This study aimed to analyze the profile of bioactive compounds in cubeb fruit, focusing on tannins, phenols, and flavonoids. Tannins are a type of polyphenol with antioxidant properties, phenols are organic compounds with various biological activities, and flavonoids are a diverse group of phytonutrients with antioxidant and anti-inflammatory effects. These compounds were extracted using different solvents, and Gas Chromatography-Mass Spectrometry (GC/MS) was employed to profile them. The results indicate that 96% ethanol is more effective at extracting compounds compared to 70% ethanol and distilled water. The percentage yield of the sun-dried cubeb extract varies significantly with different solvents (P<0.05). Quantitative analysis of cubeb fruit extracts demonstrated that flavonoid content was highest with 96% ethanol (27.85±0.53 mg QE/g), followed by 70% ethanol (10.84±0.34 mg QE/g) and distilled water (2.39±0.03 mg QE/g). Total phenol content was also greatest with 96% ethanol (45.23±0.23 mg GAE/g), compared to 70% ethanol (36.04±0.33 mg GAE/g), and distilled water (12.60±0.42 mg GAE/g). For tannins, 96% ethanol yielded the highest concentration (27.85±0.25 mg TAE/g), with lower levels in distilled water (7.81±0.32 mg TAE/g) and 70% ethanol (6.56±0.07 mg TAE/g). These significant differences (P<0.05) highlight the potential of cubeb fruit as a valuable source of bioactive compounds, suggesting its suitability for functional food applications.